ANALISIS PELAKSANAAN TEORI PROGRESIVISME JOHN DEWEY DALAM PEMBELAJARAN PENDIDIKAN AGAMA KRISTEN - Novarita Novarita; Rosmilani Rosmilani; Agnes Agnes; Irmania Jome’; Eta’ Tikadang (CV. ADIBA AISHA AMIRA, 2023)
The progressive theory developed by John Dewey has become a fundamental cornerstone in modern education. This theory emphasizes experience, reflection, and learning that is relevant to everyday life. In the context of Christian religious education, the application of progressive theory raises questions about how these principles can be integrated into religious instruction that encompasses spiritual and moral dimensions. This research analyzes the implementation of John Dewey's progressive theory in the teaching of Christian religious education. A qualitative approach is employed using a case study method in several Christian religious educational institutions. Data is gathered through classroom observations, interviews with teachers and students, as well as content analysis of instructional materials. The results of the analysis demonstrate that the application of progressive principles in Christian religious education can yield positive impacts. The use of experimental and interactive methods enables students to develop their understanding of Christian teachings through direct experiences. Problem-based learning triggers profound reflections on the moral implications in everyday life, while a collaborative approach facilitates rich discussions on religious issues. The analysis also indicates that the implementation of John Dewey's progressive theory in teaching Christian religious education holds the potential to enhance student comprehension and engagement. However, a careful balance between empirical experience and spiritual dimensions is necessary to achieve a holistic Christian religious education goal. Further research could explore concrete strategies to address these challenges and develop a balanced holistic approach to instruction.